Doses de nitrogênio e estoque de carbono no solo em plantio direto e plantio convencional na produção de hortaliças - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2016)
Nitrogen is the most required nutrient in crops, as it acts in the synthesis of several compounds essential to the development of plants. The objectives of this work were: to evaluate the effect of nitrogen rates on yield and carbon stock in the soil for zucchini and cabbage cultivated under conventional tillage and no - tillage systems. The experiments were conducted at Fazenda Escola Capão da Onça (FESCON) belonging to the State University of Ponta Grossa, located in Ponta Grossa - PR, in the year 2014 for the cultivation of zucchini and 2015 for the culture of cabbage. Two tillage systems were used: conventional tillage (PC) and no-tillage (PD), where each one represented one experiment. For each experiment, the experimental design was a randomized block with four replicates and five nitrogen doses: 0; 20; 40; 60 and 80 kg ha-1 for zucchini and 0; 70; 140; 210 and 280 kg ha-1 for cabbage, with urea being the source of nitrogen used. For the culture of the zucchini were evaluated characteristics of diameter and length of the fruit; Number, fresh and dry mass of leaves; Leaf area index; Number of male and female flowers; Percentage of fruit setting; Number of fruits per plant; Fresh fruit mass and productivity. For the cabbage crop were evaluated the characteristics of number, fresh and dry mass of the leaves of the skirt; Leaf area index; Fresh mass, longitudinal and transverse head diameter; Format index; Length of heart and productivity. For the two experiments the soil carbon stock (0-10, 10-20 and 20-40 cm depth) was determined following the methodology proposed by Ghani; Dexter; Perrott (2003) for carbon extracted from hot water (C-AQ) and Tirol-Padre; Ladha (2004) for the carbon extracted by potassium permanganate (C-OXP). For the cultivation of zucchini, in a conventional planting system, nitrogen promoted an increase of both vegetative and reproductive. Plants submitted to dose 62,16 kg ha-1 of N presented higher leaf mass dry mass values. The highest values for the characteristics of number of female flowers, percentage of fruit glue and number of fruits per plant were obtained with 41,23; 47,41 and 42,45 kg ha-1 of N, respectively. The dose of 51, 49 kg ha-1 yielded the maximum yield (31,45 t ha-1) with an increase of 13,26 t ha-1 relative to the control. In the cabbage crop under conventional tillage system, nitrogen promoted a quadratic increase for all characteristics evaluated. With the application of 247,60 kg ha-1 N, yields of 51.92 t ha-1 were obtained, presenting an increase of 30,66 t ha-1 when compared to dose 0. For zucchini (48,13 g) was obtained with the 55,73 kg ha-1 N dose, representing an increase of approximately 58% in relation to the absence of nitrogen. The highest values for the characteristics of number of female flowers, percentage of fruit setting and number of fruits per plant were obtained with 48,38; 48,88 and 46,44 kg ha-1 N, respectively. The maximum yield (17,29 t ha-1) was obtained with the dose of 48,42 kg ha-1 of N, obtaining an increase of 14,07 t ha-1 in relation to dose 0. For cabbage in system of no-tillage, significant responses were obtained for all traits analyzed as a function of N doses. The application of 24,33 kg ha-1 N, yielded a productivity of 40,53 t ha-1, presenting an increase of 35,53 t ha-1 when compared to dose 0. For crops of zucchini and cabbage in conventional tillage, the doses of 51,49 kg ha-1 and 247,60 kg ha-1 provided the highest yields, respectively. For the cultivation of zucchini and cabbage in no-tillage, the yields of 48,42 kg ha-1 and 243,33 kg ha-1 provided the highest yields, respectively. For the two experiments, no significant effect of N rates on soil carbon stocks was observed.
Nitrogen doses and carbon stoks in the soil in no tillage an conventional tillage in the vegetable cpros production
Keywords: Cucurbita pepo; Brassica oleracea var; capitata; plantio direto e convencional; Nitrato; Fração lábil do carbono; Cucurbita pepo; Brassica oleracea var; capitata; no-tillage and conventional; nitrate; labile SOC; CNPQ::CIENCIAS AGRARIAS::AGRONOMIA